ANALYSIS OF CONSUMER CHOICE FACTORS IN CHOOSING DIGITAL PHOTO GRAPHICS IN THE MIDST OF A PANDEMIC IN LOMBOK: EXPLORING DISAPPEARING DECISIONS - Ety Nurhayaty; Dede Suleman; Etik Dwi Styaningrum; Roydawaty Bunga; Aprilia Puspasari; Supriatin; Enggar widianingrum (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine the factors that shape consumer purchasing decisions on Digital Photo Graphics. Variables that are assumed to form consumer loyalty are price, product, service, place, promotion, presentation and reputation. Researchers used quantitative descriptive research. The population in this study are consumers who shop at Digital Photo Graphics in 2020. The sample in this study is consumers who meet the criteria set by the researchers with a total of 83 people. The analytical method used in this study is explanatory factor analysis (EFA) with the help of the SPSS application. The results of this study indicate that 5 factors are formed, namely Excellent Service Factors (1), Store Convenience Factors (2), Accessibility Factors (3), Product Performance Factors (4), Promotion Factors (5). The Excellent Service factor has the highest variance value, which is 46%. Steps that can be taken by Digital Photo Graphics are increasing up-selling, making company uniforms, providing personal service, making terms and conditions, cutting dense trees, directing parking to be neater, making product quality consistent, allocating funds for research & development, active on social media and giving discounts to loyal customers.